The Effects of Melatonin On The Oxidative Stress , Protein Glycation , Microalbuminuria and Lipid Profile In Type II Diabetes Mellitus - M.H. Al–Mhbashy, Hasan; A. Hussain, Saad; A.M. Numan, Nawfal; A. Saed, Majeed (Iraqi Journal of Pharmaceutical Sciences, 2017)
Previous studies indicated that supplementation with antioxidants has a protective effects against oxidative stress–induced damage in type 2 diabetes. In this study we evaluated the antioxidant effects of melatonin on the oxidative stress parameters and microalbuminuria in type 2 DM patients. 30 patients with type 2 DM were treated with 3mg/day melatonin for 90 days. Erythrocytes and plasma MDA and glutathione, fasting plasma glucose, %HbAIC, microalbuminuria, total plasma protein and lipid profile were measured each 30 days and compared with those obtained from 20 healthy controls. A decrease in MDA levels associated with the elevation in GSH levels were observed, compared with the pre–treatment levels. Fasting plasma glucose, glycated hemoglobin and microalbuminuria were significantly decreased, associated with an improvement in the total cholesterol, HDL–C and LDL–C levels, with respect to the pretreatment values.In conclusion , treatment of type 2 DM patients with melatonin may have protective effects against the oxidative stress–induced damage during the course of type 2 DM. Key words: Diabetes Mellitus, Oxidative Stress, Melatonin,Microalbuminuria.